Copper partitioning in mid-Miocene flood basalts from the Northern Great Basin (U.S.A): implications for Cu behavior in flood basalt provinces - Wierman, Christopher Thomas (Kansas State University, 2018)
It is generally accepted that beneath flood basalt provinces, Cu-Ni-PGE sulfide deposits may be found (Ridley, 2013). The focus of this study is the Steens Basalt, a mid-Miocene flood basalt from the northern Great Basin (USA) which contains between ~5-400 ppm copper and is characterized by large plagioclase phenocrysts, some of which can contain primary inclusions of copper despite the chalcophile nature of Cu (Hofmeister and Rossman, 1985; Johnston et al., 1991). The purpose of this project is to identify the distribution of Cu among coexisting phases in Steens Basalt, test whether plagioclase crystals in Steens lavas can host Cu, even when Cu is not visible, and test whether sulfide minerals/droplets are present in Steens Basalt samples with low Cu concentrations. Samples of Steens lavas were examined for sulfide minerals via reflected light microscopy, Raman spectroscopy, and X-ray diffraction with a molybdenum tube. Using an electron microprobe, silicate minerals, oxides, glass, and sulfides were analyzed for their Cu concentration, as well as other major and trace element chemistry. Glass did not contain detectable Cu which precluded partition coefficient (Kd) calculations. Based on average Cu concentration for the non-sulfides, magnetite contains the most Cu, followed by (forsteritic) weathered olivine, pyroxene, olivine, plagioclase, and ilmenite. Copper sulfides were discovered in samples MB97-19 and MB97-76C with additional non-copper sulfides in MB97-76B. In conclusion, these results lay the groundwork for further investigation into potential copper sulfide reserves in the magma plumbing as with other flood basalt packages linked to economically important mineral deposits.
Keywords: Copper; Plagioclase; Oregon sunstones; Immiscible sulfide textures; Flood basalt